THE EFFECT OF FINANCIAL LITERACY, FINANCIAL ATTITUDE, AND PERCEIVED RISK ON FINANCIAL MANAGEMENT BEHAVIOR IN USING BUY NOW PAY LATER (BNPL) - Retnaningrum, Kartika; Siti Sundari (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
This study focuses on inspecting the influence of financial literacy, financial attitudes, also perceived risk on the financial management behavior of BNPL users through a quantitative approach. The study population includes Generation Z and Millennials (aged 20–34) who are BNPL users in Surabaya. The sampling technique employed was random sampling, resulting in 166 respondents. Data was collected via an online questionnaire (Google Form) and inspected utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM). The study outcomes revealed that financial literacy, financial attitudes, and perceived risk influence financial management behavior among BNPL users in the Generation Z and Millennial populations in Surabaya. The better the financial literacy, financial attitudes, and perceived risk, the more it encourages rational, wise, and controlled financial management behavior when utilizing BNPL. This research contributes to the literature on the application of prudent financial management behavior in the usage of BNPL. It provides input for the government and service providers in formulating regulations that support the effective development of BNPL fintech.